2021
DOI: 10.1002/gps.5588
|View full text |Cite
|
Sign up to set email alerts
|

A 6‐year prospective clinical cohort study on the bidirectional association between frailty and depressive disorder

Abstract: Introduction: Depressive disorder has been conceptualised as a condition of accelerated biological ageing. We operationalised a frailty index (FI) as marker for biological ageing aimed to explore the bidirectional, longitudinal association between frailty and either depressive symptoms or depressive disorder. Methods:A cohort study with 6-year follow-up including 377 older (≥60 years) outpatients with a DSM-IV-defined depressive disorder and 132 never-depressed controls. Site visits at baseline, 2 and 6-year f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
3
10
0
2
Order By: Relevance
“…The studies listed in Table 1 represent those on frailty trajectories in older populations. However, in the field of frailty trajectories, more specific research directions are evolving, such as work in specific patient populations (e.g., psychiatry and oncology), 41 , 42 ) latent frailty trajectories (i.e., groupings of people based on distinct frailty trajectories), 43 ) frailty fluctuations (i.e., within-person deviations from general frailty trajectories), 10 ) the order in which frailty components develop, 44 ) and terminal decline in frailty. 45 , 46 )…”
Section: Changes In Frailtymentioning
confidence: 99%
“…The studies listed in Table 1 represent those on frailty trajectories in older populations. However, in the field of frailty trajectories, more specific research directions are evolving, such as work in specific patient populations (e.g., psychiatry and oncology), 41 , 42 ) latent frailty trajectories (i.e., groupings of people based on distinct frailty trajectories), 43 ) frailty fluctuations (i.e., within-person deviations from general frailty trajectories), 10 ) the order in which frailty components develop, 44 ) and terminal decline in frailty. 45 , 46 )…”
Section: Changes In Frailtymentioning
confidence: 99%
“… 37 , 38 Yet, using data of the Netherlands Study of Depression in Older persons (NESDO), we showed that frailty at baseline was highly predictive of premature mortality among depressed older patients, irrespective whether frailty was operationalized according to the frailty phenotype criteria 39 or the deficits accumulation model underlying the frailty index. 40 In sum, these studies support the (predictive) validity of frailty assessment in depression and thus for risk stratification in geriatric mental health care. In the second part of this review, implications for treatment will be discussed.…”
Section: Epidemiologymentioning
confidence: 54%
“…A study in US women also applied reduced rank regression (using CRP, IL-6 and TNF-A as response variables) and found that higher scores in inflammatory dietary patterns, including sugary beverages, refined grains, red meat, dietary soft drinks, margarine, and other vegetables and fish, were associated with higher depressive symptoms. In addition, three studies using prior DII observed a statistically significant positive association between higher DII scores and higher depressive symptoms 28 29…”
Section: Discussionmentioning
confidence: 99%